TECHNOLOGY AND METACOGNITIVE AWARENESS IN ENGLISH COMMUNICATION AT THE WORKPLACE - Almanar, Muhammad Abduh; Mayuni, Ilza; Murtadho, Fathiaty (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the role of metacognitive awareness in language competence among professionals in workplace communication. Metacognition, the ability to monitor and regulate one’s cognitive processes, is increasingly recognized as a critical factor in effective language use, especially in complex professional environments. This research examines how metacognitive strategies—such as planning, monitoring, and evaluating—affect language performance in various professional settings, including corporate meetings, negotiations, and client interactions. The findings reveal that self-regulation and metacognitive strategies play a significant role in enhancing employees’ ability to communicate effectively in English, particularly in global business contexts. Participants demonstrated a strong metacognitive awareness, with a mean score of 4.13 for their ability to adjust communication strategies in professional interactions. Similarly, the reflection on task performance and goal-setting yielded mean scores of 4.00 and 4.07, respectively, indicating that employees actively engage in self-regulatory behaviours to improve their English communication skills. Besides, individuals’ metacognitive also maintaining balance and self-regulated in utilizing technology.